The shape of the ruins - Vásquez, Juan Gabriel, 1973- (Riverhead Books, 2018)
The Shape of the Ruins is a masterly story of conspiracy, political obsession, and literary investigation. When a man is arrested at a museum for attempting to steal the bullet-ridden suit of a murdered Colombian politician, few notice. But soon this thwarted theft takes on greater meaning as it becomes a thread in a widening web of popular fixations with conspiracy theories, assassinations, and historical secrets; and it haunts those who feel that only they know the real truth behind these killings. This novel explores the darkest moments of a country's past and brings to life the ways in which past violence shapes our present lives. A compulsive read, beautiful and profound, eerily relevant to our times and deeply personal, The Shape of the Ruins is a tour-de-force story by a master at uncovering the incisive wounds of our memories.